PENGARUH KEPEMIMPINAN MOTIVASI DAN KEPUASAN KERJA TERHADAP KINERJA KARAWAN PT ASTRA MULTI TRUCKS INDONESIA - Yudhi Hardiansyah; Ari Pradhanawati; Sri Suryoko (Universitas Diponegoro, 2014)
Human resource is one of factors which has important role in developing employment performance. To bear in mind the importance of human resource, thus, a company should pay attention to the factors which work onto human resource in working; one of the is a good leadership. Therefore, the employers could work precisely in its standard and no error. In other hand, motivation is also very important, because it is one of a supportive working factors in a company. Since the employees get work satisfaction, hence, their performance will get better. This research is aimed to get to identify the influence of leadership, motivation and working satisfaction variable toward employment performance in PT Astra Multi Trucks Indonesia. The population of this research is the 75 employees of PT Astra Multi Trucks Indonesia which its questionnaires were distributed by census method. Its measurement scale uses Likert scale and its data analysis uses simple linear regretion test and double regretion test with SPSS 15.0 program. From the analysis result, it is known that the leadership, motivation and working satisfaction are working, in addition, the employees performance is excellent. Leadership variable plays role towards employees performance up to 48.4 %. Motivation variable influences employees performance up to 46.8 %. Working satisfaction variable influences employees performance up to 45 %. Thus, statistically, leadership, motivation and working satisfaction towards employees performance is 49.2%. It is expected that the better leadership, motivation and working satisfaction will create the better employee performance. According to this research result, PT. Astra Multi Trucks Indonesia management needs to pay attention to the leadership which is undergoing in the company. It can be conclude that a good, tough and wise leadership should be kept up to keep a good work from the employees and also to improve their performance which is click with that the company wants. The satisfaction of the employees is necessary to be considered, moreover, the satisfaction related with the boss toward the workers; each worker and also the working enviroment. A good harmony in a company must be created and improved to make a condusive working enviroment.